The Electronic Contracting of Financial Services: Characteristics and Main Legal Implications - Yuta González, Maria del Carmen (2015)
The first part of the article seeks to highlight the importance that increasingly electronic trading experience in the field of financial services, and as a result of that the new expressions that arise in providing financial transactions through a conceptual distinction of services and financial channels. In this context, new challenges for the industry players requiring them continuing specialization and innovation in product design, in order to satisfy the current demands ofconsumers who have configured one profile increasingly informed, sophisticated technology in making their consumption decisions.In the second part of the article, I will describe the local regulation which applies to electronic contracting in comparison with the regulation that applies to the traditional contracting which use printed information and oral presentations. This section identifies also the main regulatory implications for the consumer and the industry, with reference of compared experiences that may be interesting to comment on the formulation of considerations if applicable.